2008
DOI: 10.1016/j.ahj.2008.01.026
|View full text |Cite
|
Sign up to set email alerts
|

Lamin A/C mutation analysis in a cohort of 324 unrelated patients with idiopathic or familial dilated cardiomyopathy

Abstract: Background-Lamin A/C mutations are a well established cause of dilated cardiomyopathy (DCM), although their frequency has not been examined in a large cohort of patients.We sought to examine the frequency of mutations in LMNA, the gene encoding lamin A/C, in patients with idiopathic (IDC) or familial dilated cardiomyopathy (FDC).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
217
0
12

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 225 publications
(241 citation statements)
references
References 28 publications
7
217
0
12
Order By: Relevance
“…Ultimately, a better understanding of the pathogenesis of the disease may suggest novel strategies targeting the underlying molecular defects. [4,5,35] c.348_349insG p.Lys117GlufsX10 AVB, AF, SCD Coil 1B [36] c.356+1G>T n/a n/a Coil 1B [37] c.357-1G>T n/a LBBB, AF, PVB, VT, VF, HF Coil 1B [4,31,34] o -atrio-ventricular block degree, in parenthesis when degree specified only in some studies; AF -atrial fibrillation; AFL -atrial flutter; AN -axonal neuropathy; ASS -atrial standstill; ATC -atrial tachycardia; AVB -atrio-ventricular block; Br -bradycardia; CA -cardiac abnormalities; CCD -cardiac conduction disease; CMT2 -Charcot-Marie-Tooth disease; DCM -dilated cardiomyopathy; DM -diabetes mellitus; EDMD(2) -Emery-Dreifuss muscular dystrophy (type 2); FPLD -familial partial lipodystrophy; HF -heart failure; IVB -intra-ventricular block; ICD -implantable cardiac defibrillator; LAFB -left anterior fascicular block; LBBB -left bundle branch block;…”
Section: Conclusion: the Mechanistic Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultimately, a better understanding of the pathogenesis of the disease may suggest novel strategies targeting the underlying molecular defects. [4,5,35] c.348_349insG p.Lys117GlufsX10 AVB, AF, SCD Coil 1B [36] c.356+1G>T n/a n/a Coil 1B [37] c.357-1G>T n/a LBBB, AF, PVB, VT, VF, HF Coil 1B [4,31,34] o -atrio-ventricular block degree, in parenthesis when degree specified only in some studies; AF -atrial fibrillation; AFL -atrial flutter; AN -axonal neuropathy; ASS -atrial standstill; ATC -atrial tachycardia; AVB -atrio-ventricular block; Br -bradycardia; CA -cardiac abnormalities; CCD -cardiac conduction disease; CMT2 -Charcot-Marie-Tooth disease; DCM -dilated cardiomyopathy; DM -diabetes mellitus; EDMD(2) -Emery-Dreifuss muscular dystrophy (type 2); FPLD -familial partial lipodystrophy; HF -heart failure; IVB -intra-ventricular block; ICD -implantable cardiac defibrillator; LAFB -left anterior fascicular block; LBBB -left bundle branch block;…”
Section: Conclusion: the Mechanistic Hypothesesmentioning
confidence: 99%
“…Lamin A/C is found in almost all cells except in certain differentiated cells of hematopoietic origins [31]. Cellular models have shown that lamin A and C proteins are found distributed together in a homogeneous meshwork.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5] Affected individuals frequently have a rapidly progressive downhill clinical course, requiring pacemaker implantation or heart transplantation, with an increased risk of sudden death. [2][3][4][5] Despite the clinical importance of LMNA mutations, very little is known about mechanisms of disease pathogenesis and strategies to prevent DCM have not been investigated.Because one-third of DCM-causing LMNA mutations are stop codons, splice site variants or insertions/deletions that reduce lamin A/C protein levels, 1,5 Lmna knockout mice are a useful and clinically relevant model to study DCM mechanisms. 6 We have previously reported that homozygous Lmna knockout (Lmna Ϫ/Ϫ ) mice exhibit severe DCM by 4 to 6 weeks.…”
mentioning
confidence: 99%
“…Patients with LMNA mutations and DCM also have electrical instability (DCM+E), with supraventricular arrhythmias and atrioventricular block (AVB) often present before systolic dysfunction. 3,24 In large DCM cohorts, LMNA mutations are present in ~5% of patients 25 , however they are more prevalent (~33%) in patients with a DCM+E phenotype. 26 Desmosome gene mutations are a known cause of arrhythmogenic right ventricular cardiomyopathy (ARVC), but may also play a role in DCM.…”
Section: Dcm Disease Genesmentioning
confidence: 99%